If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 8x + 4 Reorder the terms: 3 = 4 + 8x Solving 3 = 4 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 3 + -8x = 4 + 8x + -8x Combine like terms: 8x + -8x = 0 3 + -8x = 4 + 0 3 + -8x = 4 Add '-3' to each side of the equation. 3 + -3 + -8x = 4 + -3 Combine like terms: 3 + -3 = 0 0 + -8x = 4 + -3 -8x = 4 + -3 Combine like terms: 4 + -3 = 1 -8x = 1 Divide each side by '-8'. x = -0.125 Simplifying x = -0.125
| -6(2+7k)=-12+4k | | 2(n-2)=2+4n | | 4(3n-2)=64 | | -16+3y=4 | | -2=-2-3(4-2k) | | 10k+3=8k+27 | | 72=6(-2+7x) | | 55=18+0.004x | | 32=4(1-7k) | | 2a+4a-13=47 | | 4x-6=3x+1-x-7 | | -5(3x+4)=2(9-6x) | | -36=6X-12Y | | 384628x+298473=2937474 | | 6(5-7n)=72 | | -13-p=-11 | | y=4865x+56743 | | (2x-4)/7=-6x | | y=4865x+1996559th | | b/16=4 | | 11t+4(1-4t)= | | 27=16+n | | 4t-10/5 | | 3n+8=5(n-5)+6 | | b+-17=-31 | | -9*5-4Y=36 | | x^2-2dx-y^2=0 | | 15=n/2 | | -9*3-4Y=36 | | (5x-2)/(5x+2)=(x+2)/(x+4) | | 6(x+2)+20x-4=8(x-2)+8 | | 3*2-6Y=-18 |